Analisis Teknik Menyusun Unsur Kalimat Untuk Meningkatkan Kemampuan Menyusun Kalimat Efektif - Suprapti Suprapti (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
This study is entitled "Analysis of Sentence Element Structuring Techniques to Improve the Ability to Compose Effective Sentences". The problems studied in this study are 1) How to improve the ability to compose sentences effectively through sentence element techniques in grade IX junior high school students 2) How did the behavior of grade IX junior high school students change during the study?. The purpose of this study was (1) to obtain an objective description of the improvement of the ability of grade IX junior high school students to construct effective sentences after the students were equipped to construct sentence elements and (2) to obtain an objective description of changes in student behavior during the study. This research was carried out in two stages, namely cycle I and cycle II stages. The subject of this study is the effective sentence ability of grade IX junior high school students, which must be skilled in language, improve the ability to think, reason, and broaden horizons, one way that can be taken is to improve the ability to compose effective sentences. The study is presented in the form of a cycle. The study was conducted in two cycles, namely cycle I and cycle II. Each cycle consists of four stages or steps. These steps are (1) planning, (2) action, (3) observation or observation, and (4) reflection. The four steps are always related to each other. Similarly, in its implementation, cycle I and cycle II are intertwined. Cycle I as a guideline in implementation between cycle II and cycle II is an improvement from cycle I. The results showed an increase in the ability to compose effective sentences through the technique of composing sentence elements was seen in the pretest results about composing sentence elements obtained by students with a grade average score of 5.85, while the pretest results about the ability to compose effective sentences with a class average score reached 6.35. The test results about sentence elements in cycle I reached an average score of 6.58 which means an increase of 0.73 or 1.83%, while the test results about effective sentences in cycle I obtained an average score of 7.59 which means an increase of 0.91 or 2.28%, while the test results about effective sentences in cycle II obtained an average score of 8.01 which means an increase of 0.42 or 1.05%. Improvements in student behavior were seen during the study. In the teaching and learning process of cycle I students who have behaved positively amounted to 23 students or 57.50%, while in cycle II the number increased to 32 students or by 80%. These positive behaviors are paying attention to the teacher, responding well to the speaker, asking questions when not clear, expressing opinions and doing assignments seriously.